Aplikasi Pendiagnosa Penyakit Mata Dengan Menggunakan Metode Certainty Factor - Muhammad Yasin Simargolang; Sri Rahmawati (Universitas Asahan, 2018)
Abstract - In today's information technology era, the need for faster and more recent information is needed, considering that information has become a very important resource for organizations that need special handling such as other resources. The eye is a member of the body that needs to be maintained in daily health. Along with the rapid development of technology, in the field of medicine today it has also utilized technology to help improve better service to the wider community. The Certainty Factor method is used to be able to make a diagnosis quickly, accurately and accurately to the symptoms of the disease caused and this method is expected to be able to help patients, especially eye diseases, without first going to the hospital. This method makes it easy for users to provide answers related to the amount of trust in the symptoms experienced. Keywords - Technology, Information, Eyes, Method of Certainty Factor.